Pengaruh Keterbukaan Ekonomi terhadap Pertumbuhan Ekonomi di Kawasan ASEAN-5 Tahun 2015-2023 - Ima Amaliah; Lasmi Aprilyani Sri Rejeki (UPT Publikasi Ilmiah Unisba, 2025)
Abstract. This study aims to analyze the impact of trade openness (TO), foreign direct investment (FDI), and exchange rate (ER) on economic growth in the ASEAN-5 countries during the 2015–2023 period. A quantitative descriptive method was employed using panel data, which combines time series and cross-section data from five ASEAN countries. The secondary data were obtained from the World Bank, and the estimation model used was the Fixed Effect Model (FEM), based on panel data testing results.The findings reveal that TO has a negative and significant effect on economic growth in the ASEAN-5. This is attributed to the high dependence on imports and the weak competitiveness of local industries. In contrast, FDI shows a positive and significant influence, as it contributes to capital accumulation, technology transfer, improved productivity, and economic capacity expansion. Similarly, ER has a positive and significant impact on economic growth, where currency depreciation enhances export competitiveness, boosts net exports, and stimulates aggregate demand.The coefficient of determination is 90.91%, indicating that TO, FDI, and ER collectively explain a substantial portion of the variation in economic growth across ASEAN-5 countries. This suggests a strong relationship between these variables and economic growth during the study period. Abstrak. Penelitian ini bertujuan untuk menganalisis pengaruh trade openness (TO), foreign direct investment (FDI), dan exchange rate (ER) terhadap pertumbuhan ekonomi di kawasan ASEAN-5 selama periode 2015–2023. Menggunakan metode kuantitatif deskriptif dengan data panel (kombinasi time series dan cross section) dari lima negara ASEAN, data diperoleh dari World Bank. Model estimasi menggunakan Fixed Effect Model (FEM) setelah melalui uji panel data. Hasil penelitian menunjukkan bahwa TO memiliki pengaruh negatif dan signifikan terhadap pertumbuhan ekonomi ASEAN-5. Hal ini disebabkan oleh ketergantungan yang tinggi pada impor serta lemahnya daya saing industri lokal. Sebaliknya, FDI berpengaruh positif dan signifikan karena mampu meningkatkan modal, transfer teknologi, produktivitas, serta kapasitas ekonomi. ER juga berpengaruh positif dan signifikan terhadap pertumbuhan ekonomi karena depresiasi mata uang mendorong daya saing ekspor, meningkatkan ekspor neto, dan permintaan agregat. Koefisien determinasi sebesar 90,91% menunjukkan bahwa ketiga variabel tersebut sangat erat hubungannya dengan pertumbuhan ekonomi di ASEAN-5. Ini mengindikasikan bahwa TO, FDI, dan ER merupakan faktor dominan yang memengaruhi pertumbuhan ekonomi kawasan tersebut selama periode yang diteliti.